2013
DOI: 10.1007/s10815-013-9969-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-chimerism and chimerism pseudo dicentric Y chromosome: two case reports about azoospermia and cytogenetic/molecular genetic analysis in the Chinese population

Abstract: Objective To report the cytogenetic and molecular genetic analysis of the first two cases of non-chimerism and chimerism karyotype in Chinese male patients who suffer from azoospermia, which may be caused by pseudo dicentric Y chromosomes. Design Case study. Setting Academic reproductive medicine center. Patients Two male patients with azoospermia, carrying pseudo dicentric Y chromosome.Interventions Review the records of inquiry, testicular biopsy, pathological examination, semen routine examination, endocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…FISH analysis was conducted with the combination of SRY and DYZ3 probes. Moreover, screening of Y chromosome deletions in two brothers were analyzed by a real-time PCR method as described previously [ 19 ]. According to the European Academy of Andrology and the European Molecular Genetics Quality Network guidelines, three selected sequence-tagged sites within specific AZFa, AZFb, and AZFc regions were chosen as targets.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…FISH analysis was conducted with the combination of SRY and DYZ3 probes. Moreover, screening of Y chromosome deletions in two brothers were analyzed by a real-time PCR method as described previously [ 19 ]. According to the European Academy of Andrology and the European Molecular Genetics Quality Network guidelines, three selected sequence-tagged sites within specific AZFa, AZFb, and AZFc regions were chosen as targets.…”
Section: Case Presentationmentioning
confidence: 99%
“…The androgen receptor gene on the long arm of the X chromosome has been found to play a role in meiosis and the conversion of spermatocytes to round spermatids during spermatogenesis [ 17 ]; while its mutation leads to androgen insensitivity syndrome and Kennedy syndrome, a neurodegenerative disorder with spermatogenesis abnormalities [ 18 ]. Moreover, mutations or partial deletions of some X-linked genes such as AKAP3 , AKAP4 , NXF2 , TAF7L , USP26 , and TEX11 are linked to male subfertility or infertility [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In GTG-banding, the presence of extra chro- mosomes or structural abnormalities in a minimum of 2 cells or missing chromosomes in 3 cells is considered as a mosaic, and in FISH, a mosaic is considered by the presence of a minimum of 2 cells with an extra signal or 3 cells with a missing signal [Okada et al, 2001]. A study was conducted in which 2 patients with a pseudodicentric Y chromosome were reported, who exhibited relatively small testes and showed an absence of sperm in their semen, but the reason for their azoospermia could be attributed to the absence of the AZFb and AZFc regions [Li et al, 2013;Nailwal and Chauhan, 2017]. Microdeletions in the AZF region are commonly observed in cases of severe oligozoospermia and azoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…The genes on the Y chromosome are particularly crucial in the process of spermatogenesis. A variety of abnormalities, such as inversions, deletions translocations, dicentric Y and isochromosome Y, can lead to varying clinical symptoms such as testicular hypoplasia or developmental malformations, severe oligozoospermia and azoospermia (Kim et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%